PDIA4, a new endoplasmic reticulum stress protein, modulates insulin resistance and inflammation in skeletal muscle - Lee, Chien-Hsing; Chiang, Chi-Fu; Lin, Fu-Huang; Kuo, Feng-Chih; Su, Sheng-Chiang; Huang, Chia-Luen; Li, Peng-Fei; Liu, Jhih-Syuan; Lu, Chieh-Hua; Hsieh, Chang-Hsun; Hung, Yi-Jen; Shieh, Yi-Shing (Frontiers in Endocrinology, 2022)
Endoplasmic reticulum (ER) stress has emerged as a key player in insulin resistance (IR) progression in skeletal muscle. Recent reports revealed that ER stress-induced the expression of protein disulfide isomerase family a member 4 (PDIA4), which may be involved in IR-related diseases. A previous study showed that metformin modulated ER stress-induced IR. However, it remained unclear whether metformin alleviated IR by regulating PDIA4 expression in skeletal muscle. Herein, we used palmitate-induced IR in C2C12 cells and a high-fat diet-induced IR mouse model to document the relations between metformin, IR, and PDIA4. In C2C12 cells, palmitate-induced IR increased inflammatory cytokines and PDIA4 expression. Besides, knocking down PDIA4 decreased palmitate-induced IR and inflammation in C2C12 cells. Furthermore, metformin modulated PDIA4 expression and alleviated IR both in vitro and in vivo. In addition, serum PDIA4 concentrations are associated with IR and inflammatory cytokines levels in human subjects. Thus, this study is the first to demonstrate that PDIA4 participates in the metformin-induced effects on skeletal muscle IR and indicates that PDIA4 is a potential novel therapeutic target for directly alleviating IR